Determinan kejadian anemia pada remaja putri di Kecamatan Gebog Kabupaten Kudus tahun 2006 - Ida Farida; Laksmi Widajanti; Siti Fatimah Pradigdo (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2014)
Background : Anemia is one of the most prevalent nutrition problems. Based on a national survey in 1995, the prevalence of anemia was 57.1% among adolescent girls in Indonesia. Adolescent girls have higher risk of anemia compared to the schoolchildren and adults as they are still in the period of rapid growing, while they also start to think about body image. Objectives: This study aimed to investigate the determinants of anemia among adolescent girls in Kecamatan Gebog, Kabupaten Kudus. Method : This observational study was conducted cross sectionally by survey method. The population was adolescent girls aged 13-18 years, with a total sample of 163 girls who were chosen from the adolescent girls in four villages by multistage random sampling method. Data were analysed by Rank Spearman correlation and Chi Square test, which then continued to multivariate analysis by logistic regression test (forward method). Result : The results showed that the prevalence of anemia among adolescent girls in Kecamatan Gebog, Kabupaten Kudus was 36.8%. The correlation tests showed that there were associations between parents’ education level, family income, adolescents’ knowledge and attitude toward anemia and food consumption levels (energy, protein, iron, vitamin A and C). Conclusion : There were correlations between food consumption levels (energy, protein, iron, vitamin A and C), menstruation pattern, infection incidence and anemia incidence (p<0.05). The determinants of anemia among adolescent girls in Kecamatan Gebog, Kabupaten Kudus were energy, iron, vitamin A consumption levels, menstruation pattern and infection incidence. Keywords:  anemia incidence, socio-economic status, food consumption levels, menstruation pattern, infection incidence, adolescents